J'accuse ! : la Vérité en Marche - Émile Zola (Editions Complexe, 1988)
A collection of articles relating to the Dreyfus Affair, written by Zola between 1897-1900, which appeared originally in "L'Aurore" and "Le Figaro". The collection was prepared by Zola himself in 1901. The introduction (p. 11-29), by H. Guillemin, gives a short description of Zola's involvement in the Dreyfus Affair. An appendix (p. 229-238) contains two other articles by Zola concerning the trial which were not included in the 1901 edition.
Droits : Source Google Books a verifier
Keywords: Degas; Bibliotheque